The Role of Parents in Overcoming Feeding Refusal and Preventing Iron Deficiency Anemia in Toddlers - Ummah, Kholifatul (EMBRIO: Jurnal Kebidanan, 2024)
Feeding refusal, commonly observed in infants, particularly during their first year of life, is when infants experience difficulty eating or refuse to eat. This can lead to nutritional deficiencies or malnutrition. Additionally, feeding refusal can be triggered by the inappropriate introduction of complementary foods regarding composition, texture, and feeding methods. Iron deficiency is the most common nutritional problem worldwide, especially in developing countries. Anemia in children is a hemoglobin level significantly below the average for their age. Based on surveys conducted by the Ministry of Health and several health reports, the prevalence of anemia in toddlers ranges from 40percent to 50percent . The results of a preliminary study conducted at Brondong Health Center, Brondong District, Lamongan Regency, from May to July 2024, found that 25percent of toddlers exhibited feeding refusal. Hemoglobin tests on these 11 toddlers revealed an average below 11 gr/dl. The research aims to determine the role of parents in overcoming food refusal and preventing iron deficiency anemia in toddlers. This study can use a quantitative approach with an observational analytical design at Brondong Health Center, Brondong District, Lamongan Regency. The population is toddlers aged 6-24 months with feeding refusal problems and their parents/mothers, with a sample size of 20 respondents. The measuring instrument used in this study is a questionnaire using the KAP scale, and the test used is the Chi-Square test. From this test, it was concluded that the p-value is 0.000, indicating the role of parents in addressing feeding refusal and anemia in toddlers at Brondong Health Center, Brondong District, Lamongan Regency.